Characteristics of Schizophrenia Patients at Kasihan II Bantul Public Health Center in 2022 - Elistiana, Dinda Ian; Aristiani, Windy; Adnan; Yuniasih, Dewi (Ahmad Dahlan Medical Journal, 2024)
Mental health problems are still a significant problem throughout the world. Schizophrenia is a form of chronic mental disorder that affects a person's ability to think, behave, manage emotions and interact with other people. Sociodemographic factors in individuals can be one of the risk factors for someone experiencing mental disorders, including schizophrenia. Therefore, knowing the sociodemographic factors of schizophrenia patients can be a way of early detection and preventive measures against the high rate of schizophrenia recurrence. This study aimed to determine the sociodemographic characteristics of schizophrenia patients at Kasihan II Bantul Public Health Center. This research is quantitative research with a descriptive observational research design. Data collection was carried out retrospectively using medical record data from 91 schizophrenia patients at Kasihan II Bantul Public Health Center in 2022. Sociodemographic data was taken and analyzed by presenting the results using frequency and proportion distribution tables. The results of the study showed that the incidence of schizophrenia at Kasihan II Bantul Public Health Center occurred most frequently in the adult age group as many as 79 subjects (86.8%), 57 subjects (62.6%) were males, 37 subjects (48.4%) had secondary education, 65 subjects (71.4%) had jobs, and 51 subjects (56%) were unmarried.